2019
DOI: 10.1002/aenm.201803699
|View full text |Cite
|
Sign up to set email alerts
|

Record Open‐Circuit Voltage Wide‐Bandgap Perovskite Solar Cells Utilizing 2D/3D Perovskite Heterostructure

Abstract: In this work, the authors realize stable and highly efficient wide‐bandgap perovskite solar cells that promise high power conversion efficiencies (PCE) and are likely to play a key role in next generation multi‐junction photovoltaics (PV). This work reports on wide‐bandgap (≈1.72 eV) perovskite solar cells exhibiting stable PCEs of up to 19.4% and a remarkably high open‐circuit voltage (VOC) of 1.31 V. The VOC‐to‐bandgap ratio is the highest reported for wide‐bandgap organic−inorganic hybrid perovskite solar c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
351
2
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 354 publications
(375 citation statements)
references
References 66 publications
13
351
2
1
Order By: Relevance
“…Importantly, new peaks at 9.0° and 13.5° were detected and an additional peak at very low angle 4.5° could be found using grazing incidence XRD (Figure S7, Supporting Information). These peaks did not correspond to the characteristic peaks of BABr located at 5.5° as reported previously . Instead, these peaks were related to the RP “quasi‐2D” perovskite (BA) 2 A n –1 Pb n (I x Br 1– x ) 3 n +1 with n = 2 as previously reported .…”
Section: Resultsmentioning
confidence: 55%
“…Importantly, new peaks at 9.0° and 13.5° were detected and an additional peak at very low angle 4.5° could be found using grazing incidence XRD (Figure S7, Supporting Information). These peaks did not correspond to the characteristic peaks of BABr located at 5.5° as reported previously . Instead, these peaks were related to the RP “quasi‐2D” perovskite (BA) 2 A n –1 Pb n (I x Br 1– x ) 3 n +1 with n = 2 as previously reported .…”
Section: Resultsmentioning
confidence: 55%
“…The relatively low open circuit voltage ( V oc ) and fill factor (FF) are the main reasons for the poorer performance of CsPbI 2 Br PSCs. As for perovskite PSCs, the energy loss ( E loss ) is defined as E loss = E g ‐ eV oc ( E g and e are bandgap and elementary charge, respectively) 16–18. High E loss linked to high defect density (large nonradiative energy loss) and mismatched bandgaps lead to the decreased V oc .…”
Section: Introductionmentioning
confidence: 99%
“…The BAI‐coated FACs device shows a slightly higher V oc (1.12 V) compared to the reference without the BAI layer (1.08 V) and the one with BAI mixed within the precursors' solutions (Figure a and Table S2, Supporting Information). Note that by depositing the BAI salt on the FACs and EA‐FACs surfaces, even though the samples were not subjected to thermal annealing, we found that a 2D phase is formed probably (see Figures S9 and S10, Supporting Information) due to a diffusion of the large cation within the first tens of seconds . In the case of EAI‐overcoating, the EAI(top)/FACs perovskite shows a similar J – V curve to the control device without an improvement in V oc (1.08 V), contrary to the increase in V oc (1.12 V) of the EA‐mixed perovskite (Figure b).…”
Section: Resultsmentioning
confidence: 82%